Implementation of Presidential Decree No. 62 of 2023 on the Implementation of the Agrarian Reform Object Land Program in Majalengka Regency - Setiapraja, Rida Maulina; Fadiyah, Syifa Nur; Sutisna, Dhea Ajeng; Hidayat, Dudung; Gunawan, Moh. Sigit (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research focuses on examining the implementation of Presidential Regulation No. 62 of 2023 on the implementation of the acceleration of agrarian reform in Majalengka Regency. The Agrarian Reform Object Land Program is aimed at the prosperity and welfare of the community. This study uses a normative juridical method with the source of data obtained using qualitative. This research aims to test the effectiveness of the implementation of Presidential Regulation No. 62 of 2023 concerning the Acceleration of Agrarian Reform and find out the obstacles to the implementation of Agrarian Reform in Majalengka Regency. The results of this study show that the implementation of Presidential Regulation No. 62 on the acceleration of Agrarian Reform in Nunuk Baru Village, Majalengka Regency, has been on target in the aspect of Asset Management. However, it is not optimal because it is not followed by Access Arrangement, while implementation obstacles include lack of socialization, budget limitations, and inadequate road infrastructure.